APPLICATION OF BIOPHYSICAL METHODS IN THE DIAGNOSIS OF ONCOLOGICAL DISEASES - Akhmadjonova Shakhzoda (Web of Journals Publishing, 2025)
The early and accurate diagnosis of oncological diseases is critical for effective treatment and improved patient outcomes. Biophysical techniques such as Nuclear Magnetic Resonance (NMR) spectroscopy and Optical Coherence Tomography (OCT) have become increasingly important in modern diagnostic practices. These methods provide non-invasive, high-resolution insights into the biochemical and structural characteristics of tissues. This article reviews the principles, advantages, and diagnostic applications of these biophysical techniques in oncology, highlighting their potential to enhance diagnostic precision and support personalized medicine.
Keywords: Biophysics, oncology, diagnostics, NMR spectroscopy, Optical Coherence Tomography, non-invasive imaging.